PENGUJIAN TEGANGAN GAGAL DAN ARUS BOCOR KABEL TEGANGAN RENDAH - , AHMAD KHAIRUDDIN LUBIS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
a Cables are an essential element in the conduct electricity. At this time, house fire often occurs due to failure of insulation and bad cable connection. These events should be avoided because it can threaten the safety of occupants and damaging equipment. Therefore, the required sufficient knowledge in selecting the appropriate low voltage cable to be used. Low voltage cable is very easy to find on the market with a variety of brands and prices. For that, in this test taken material samples from cables are widely sold in the market, especially the city of Yogyakarta. That cables are NYM cables 2 x 1.5 mm 2 300/500 volts with trademark champion, eterna, and supreme. The purpose of this study was to determine the breakdown voltage of the AC, dielectric strength and leakage current from each of the test material. For the results of this study are expected to be a reference for the insulation capability of the three cables are tested so consumers can choose which one is the best cable to use with compare the results. cable has a higher This study begins with the measurement of the thickness dimension of the cable, then test the breakdown voltage, dielectric strength and leakage current. The test results stated that supreme breakdown voltage and dielectric strength than the champion and eterna cable. This means supreme cable has better insulating capability when compared to champion and eterna cable, just that the supreme cable has price is more expensive than both.